Electrostatic solitary waves observed at Saturn by Cassini inside 10 Rs and near Enceladus. Issue 8 (28th August 2015) - Pickett, J. S.; Kurth, W. S.; Gurnett, D. A.; Huff, R. L.; Faden, J. B.; Averkamp, T. F.; Píša, D.; Jones, G. H.
Abstract We have analyzed the Cassini Radio and Plasma Wave Science Wideband Receiver (WBR) data specifically looking for the presence of bipolar electrostatic solitary waves (ESWs). Typical examples of these ESWs are provided to show that when they are present, several of them may be detected over a few to several millisecond time span. We carried out an event study of an Enceladus encounter which took place on 9 October 2008. Approximately 30 min prior to and during the crossing of the Enceladus dust plume, several ESWs are observed with amplitudes of about 100 μV/m up to about 140 mV/m, and time durations of several tens of microseconds up to 250 µs. The highest amplitudes (over 10 mV/m) were observed only during the closest approach to Enceladus. We also carried out an ESW survey using the WBR for all years from 2004 to 2008 for distances less than 10 Rs. The survey clearly shows that most of the ESWs are found on the nightside, with a high percentage of them in the range of 4–6 Rs. This location is consistent with the densest part of Saturn's E ring and Enceladus' orbit. These are the first extended survey results of ESWs near Saturn and the first reported ESWs in connection with Enceladus. We discuss possibilities for the generation of these nonlinear ESWs, which involve current, beam, and acoustic, including dust, instabilities.